O trabalho infantil rural na Amazônia paraense, Abaetetuba-PA: diálogos pertinentes - FERREIRA, Renata Lopes (2022)
The study had as its theme "Rural child labor in Pará, amazon region, in the municipality of Abaetetuba/PA: initial considerations", in order to understand child labor from the rural reality of Abaetetuba, taking into account the rights of children and adolescents. It was based on the following guiding questions: what specificities characterize child labor in the rural context in the municipality of Abaetetuba-PA? How does the exploitation of the labor force of children and adolescents take place in this rural Amazonian context and what are the visible/real implications for human and educational development? The study was consolidated in the qualitative research approach, encompassing the bibliographic character based on references such as Rizzini (2010), Marx (1983), Souza (2014), Rodrigues (2015), Pojo (2017), Sanches (2014), Peres (2018), Andrade et. al. (2018), Arroyo (2017) among other authors, used to discuss the following axes: Labor, child labor, rural child labor in Para, Amazon region and educational demands, children and childhood in Para, Amazon region and etc .; Documentary aiming to catalog information and data on issues of the theme within reports and others, and the field, with the use of interviews and online meetings with people who live and work in the rural context of the municipality. As part of the results, we can say that rural child labor is incisively present in the Amazon context, precisely in the municipality of Abaetetuba, which presents weaknesses in human development in general, which reflect the economic, social, educational and political conditions of that context. On the other hand, the involvement of children in the world of work also comes close to cultural issues whose teachings are passed on to younger people by the closest adults, without first violating their rights.